2022
DOI: 10.21248/l1esll.2022.22.1.375
|View full text |Cite
|
Sign up to set email alerts
|

How relevant is it? Public Elementary School Teachers Encounter Ancient Jewish Texts

Abstract: This study deals with a learning encounter in a havruta (pair) setting of teachers of public elementary schools in Israel with an ancient legend (Aggadah) drawn from sixth-century Jewish culture. The objective of this study is to examine the teacher’s attitude to the text through a study of the dialogue created in the encounter with the text in the havruta setting. Participants in the study included two groups of mostly women teachers of Hebrew language (L-1): 15 teachers in Group 1, and 14 teachers in Group 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…In a previous study, we found that teachers in secular schools had four main difficulties with processing the ancient text: (a) linguistic difficulties-many unfamiliar words that are differ from modern in terms of grammar, syntax as well as lexical items and meanings; (b) structural difficulties-the structure does not always mention the personal pronoun, the subject of the verb, saying for example "said to them," or "said to him" without telling us who talked to whom; (c) lack of prior knowledge needed to understand the text, such as historical and biblical or geographic knowledge; and (d) lack of identification with the characters (Teomim-Ben Menachem & Elkad-Lehman, 2022). Due to its considerable complexity, significant effort must be invested to understand all the meanings and nuances of the text's language, structure, content and logic, and learning in a havruta can help cope with those challenges.…”
Section: Challenges In Learning Ancient Hebrew Textsmentioning
confidence: 99%
“…In a previous study, we found that teachers in secular schools had four main difficulties with processing the ancient text: (a) linguistic difficulties-many unfamiliar words that are differ from modern in terms of grammar, syntax as well as lexical items and meanings; (b) structural difficulties-the structure does not always mention the personal pronoun, the subject of the verb, saying for example "said to them," or "said to him" without telling us who talked to whom; (c) lack of prior knowledge needed to understand the text, such as historical and biblical or geographic knowledge; and (d) lack of identification with the characters (Teomim-Ben Menachem & Elkad-Lehman, 2022). Due to its considerable complexity, significant effort must be invested to understand all the meanings and nuances of the text's language, structure, content and logic, and learning in a havruta can help cope with those challenges.…”
Section: Challenges In Learning Ancient Hebrew Textsmentioning
confidence: 99%